Implementasi Jurnal Anak Sebagai Kolaborasi Guru Dan Orang Tua Dalam Pengawasan Perkembangan Siswa Sd - Eka Diah Nur Apriliani; Arta Mulyo Budi Harsono; Ahmad Suriansyah (CV. ITTC INDONESIA, 2025)
Monitoring child development at the elementary school level requires the active and synergistic involvement of two main parties: educators and parents. Elementary school-aged children are in a golden period for building a foundation of knowledge, social, emotional, and independent skills that cannot be obtained solely thru interaction at school; consistent monitoring at home is also necessary. This research aims to describe how the Children's Journal functions as a collaborative medium for comprehensively monitoring student development at SDN Tatah Mesjid 2. Using a qualitative approach with a case study method, data collection was conducted thru observation, participant observation, in-depth interviews with two classroom teachers and the school principal, supported by documentation of evidence from the Children's Journals over several months. The research findings indicate that the Children's Journal is effective as a two-way communication tool, enabling educators and parents to share information about children's behavior, responsibilities, social interactions, and emotions both at school and at home. Thru this Children's Journal, educators can identify developmental obstacles and adjust their coaching approach, while parents gain a real understanding of their responsibility to monitor their children's development and teach them discipline. Irregular journal entries by some parents are a problem, but teacher guidance can solve it. The Children's Journal serves as an educational communication tool that strengthens cooperation between home and school.